Angiogenic factor-driven improvement of refractory thin endometrium with autologous platelet-rich plasma intrauterine infusion in frozen embryo transfer cycles - Shin, So Yeon; Chung, Nanum; Shin, Ji Eun; Kim, Jee Hyun; Park, Chan; Kwon, Hwang; Choi, Dong Hee; Lee, Jung Ryeol; Kim, Ji Hyang (Frontiers in Endocrinology, 2024)
Objective: Beneficial effect on endometrial thickness (EMT) and improvement of pregnancy outcome after intrauterine infusion of Platelet-rich plasma (PRP) has been suggested. This study was to assess the effect of intrauterine PRP infusion on live birth rate, obstetrical outcomes and analyze cytokines which can potentially improve pregnancy outcome through PRP.Method: This study was a prospective cohort study conducted in a university hospital fertility center. The study included ninety-one patients who had a history of two or more failed in vitro fertilization (IVF) attempts and refractory thin endometrium that remained unresponsive after at least two conventional treatments for thin endometrium. Patients were treated with intrauterine infusion of autologous PRP between cycle days 7 and 14 during their hormone replacement therapy-frozen embryo transfer (HRT-FET) cycle. PRP was administered at 3-day intervals until the EMT reached 7mm. After a maximum of three PRP administrations, embryo transfer (ET) was performed. Primary outcomes were the live birth rates. Secondary outcomes included the implantation rate and increase of endometrial thickness (EMT) compared to the previous cycle. We compared the cytokines related to angiogenesis in a patient's whole blood (WB) and PRP by utilizing a commercial screening kit.Results: The live birth rate in the PRP treatment cycle was 20.9% (19 of 91 patients), significantly superior to the previous cycle without PRP infusion (p < 0.001). The implantation rate was also significantly higher during the PRP treatment cycle (16.4%) compared to the previous cycle (3.1%) (p < 0.001). The mean EMT post-PRP treatment was 6.1 mm, showing a significant increase of 0.8 mm (p < 0.001). Nonetheless, an increase in EMT was also observed in the non-pregnancy group. No adverse effects were reported by patients treated with autologous PRP. Cytokine array analysis confirmed marked increases in well-known pro-angiogenic factors such as Ang-1, EGF, LAP (TGF-b1), MMP-8, PDGF-AA, and PDGF-AB/PDGF-BB.Intrauterine PRP infusion offers a safe and effective treatment for patients with refractory thin endometrium and implantation failures. The angiogenic cytokines present in PRP are the primary drivers of this improvement.